2016
DOI: 10.5194/amt-9-195-2016
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluated Canadian ozonesonde record: measurements of the vertical distribution of ozone over Canada from 1966 to 2013

Abstract: Abstract. In Canada routine ozone soundings have been carried at Resolute Bay since 1966, making this record the longest in the world. Similar measurements started in the 1970s at three other sites, and the network was expanded in stages to 10 sites by 2003. This important record for understanding long-term changes in tropospheric and stratospheric ozone has been re-evaluated as part of the SPARC/IO 3 C/IGACO-O 3 /NDACC (SI 2 N) initiative. The Brewer-Mast sonde, used in the Canadian network until 1980, is dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 66 publications
2
98
0
Order By: Relevance
“…These changes began in the mid-1990s and played a role in the analysis of ozonesonde data between then and the late 2000s (Mercer et al, 2007;Tarasick et al, 2016). Recognizing that these differences exceeded the accuracy and precision that is possible from ozonesondes (Smit et al, 2007;Deshler et al, 2008) led many investigators to independently explore the differences that occur when the same ozonesonde is operated with differing solution concentrations and when differing ozonesonde types are operated with the same solution concentrations (Johnson et al, 2002;Kivi et al, 2007;Smit et al, 2007;Deshler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes began in the mid-1990s and played a role in the analysis of ozonesonde data between then and the late 2000s (Mercer et al, 2007;Tarasick et al, 2016). Recognizing that these differences exceeded the accuracy and precision that is possible from ozonesondes (Smit et al, 2007;Deshler et al, 2008) led many investigators to independently explore the differences that occur when the same ozonesonde is operated with differing solution concentrations and when differing ozonesonde types are operated with the same solution concentrations (Johnson et al, 2002;Kivi et al, 2007;Smit et al, 2007;Deshler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The absorption efficiency has been measured in the laboratory with two ECC ozonesondes measuring in series. These tests have shown that the absorption of ozone is somewhat dependent on the amount of solution used (e.g., 2.5 mL vs. 3.0 mL; Tarasick et al, 2016;Davies et al, 2003), with the absorption increasing from 0.96 as the amount of solution increases from 2.5 mL. The increase of the gas diffusion rate during balloon ascent due to the pressure decrease should limit this ozone conversion efficiency loss to the lower part of the profile (Davies et al, 2003).…”
Section: Ecc Ozonesonde Principlesmentioning
confidence: 99%
“…Additionally, this radiosonde change also caused a change in the Vaisala interface card and hence the pump temperature sensor, so that an effect on the recorded pump temperatures cannot be excluded (see Fig. 2 in Van Malderen et al, 2014, which shows a 2 • C decrease at 700 hPa). Since this effect is not quantified, no correction can be applied.…”
Section: O3s-dqa Correctionsmentioning
confidence: 99%
“…This exercise should result in an improved ozonesonde record with a reduced uncertainty (from 10-20 % down to 5-10 %), giving more solid information about the atmospheric changes that have occurred, as well as a better dataset for comparison with satellite measurements. The Canadian ozonesonde record has recently been re-evaluated regarding the O3S-DQA principles and the results are presented in Tarasick et al (2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation